Ion-exchange purification and structural characterization of five sulfated fucoidans from brown algae. (11th July 2020) - Sichert, Andreas; Le Gall, Sophie; Klau, Leesa Jane; Laillet, Brigitte; Rogniaux, Hélène; Aachmann, Finn Lillelund; Hehemann, Jan-Hendrik
Abstract: Fucoidans are a diverse class of sulfated polysaccharides integral to the cell wall of brown algae, and due to their various bioactivities, they are potential drugs. Standardized work with fucoidans is required for structure–function studies, but remains challenging since available fucoidan preparations are often contaminated with other algal compounds. Additionally, fucoidans are structurally diverse depending on species and season, urging the need for standardized purification protocols. Here, we use ion-exchange chromatography to purify different fucoidans and found a high structural diversity between fucoidans. Ion-exchange chromatography efficiently removes the polysaccharides alginate and laminarin and other contaminants such as proteins and phlorotannins across a broad range of fucoidans from major brown algal orders including Ectocarpales, Laminariales and Fucales . By monomer composition, linkage analysis and NMR characterization, we identified galacturonic acid, glucuronic acid and O-acetylation as new structural features of certain fucoidans and provided a novel structure of fucoidan from Durvillaea potatorum with α-1, 3-linked fucose backbone and β-1, 6 and β-1, 3 galactose branches. This study emphasizes the use of standardized ion-exchange chromatography to obtain defined fucoidans for subsequent molecular studies.